The Effect of Age on Death Disgust: Challenges to Terror Management Perspectives - Daniel M.T. Fessler; C. David Navarrete (Evolutionary Psychology, 2005)
Proponents of Terror Management Theory (TMT) argue that many facets of disgust serve to defend against existential anxiety accompanying cognizance of one's mortality. Because the passage of time brings death closer, this view predicts that the intensity of disgust elicited by reminders of death should increase with age. Skeptical of TMT, we conducted Internet-based studies using the instrument created by TMT proponents. Results reveal that age is negatively, not positively, correlated with death disgust sensitivity, a pattern consistent with adaptive habituation rather than terror management. The same result was obtained using in-person administration of the instrument in Costa Rica, a society characterized by attitudes toward death that differ from those of the U.S. Additional work in Costa Rica demonstrated that, contrary to TMT predictions, attention to one's own death need not increase disgust reactions to the body or its products. Both the evocative power of death stimuli and the negative effects of age on death disgust are consistent with the argument that disgust is an adaptation motivating disease avoidance rather than a psychodynamic defense mechanism.